Técnicas de agricultura de precisão para definição de zonas de manejo de solo - Hauschild, Fabio Evandro Grub (2013)
Precision farming (AP) is a technological tool that assesses the attributes of productivity constraints, it aims to reduce the spatial variability of the area, with the increase of productivity, and offering other benefits such as reduced use of fertilizers and liming, with obvious positive actions to the environment. Besides, knowledge of the properties and characteristics of soil are very important to obtain high productivity, a system where the soil is anisotropic, evidenced in the vertical direction, characterized by differentiation of layers, called horizons. The determination of management zones from physical attributes and data productivity enables the farmer to combine informations and consequently handle the area according to its soil conditions. Thereby, this technology intends to homogenize the spatial variability being in the area aiming of increased production, with efficient use of fertilizers, liming, seed and agrochemicals. The objective of this research was to determine, through maps and compression yield maps, different areas of management in clay soils in the region of Coopatrigo´s scope in the city of São Luiz Gonzaga. The research was conducted at many stages, such as georeferenced soil sampling to obtain data for penetration resistance, using equipment of Penetrolog Falker Company. Productivity data were obtained with a harvester equipped with DGPS guidance system and monitor harvest. An analysis of data and interpretation with creating maps of compaction and productivity, with the use of the CR Campeiro. The determination of the management zones was obtained by interpolation of data from the data penetration resistance of productivity, thus defining homogeneous zones with physical characteristics and productivity coincide. According to the results obtained, the correction of the chemical attributes, both pH, phosphorus, potassium, base saturation, through the process of AP provide positive results, making the homogenization of attributes. It was possible to find that the variability increases with depth, apart of the measured variable. The results of the penetration resistance betoken the existence of a compacted layer formed from seven inches depht. Furthermore, prevailing variability in the area indicates areas of superior compression, accurately in the zones where productivity is inferior. With the overlapping of maps of penetration resistance and yield maps was possible to create high, medium and low management zones, considering the interaction of these factors.Thus,the area management could be performed in a localized manner allowing the farmer to intervene improving the physical characteristics of the soil, orby the use of scarification, orby use of cover crop such as fodderturnip.